Optical control of the density and spin spatial profiles of a planar Bose gas. (30th April 2021) - Zou, Y-Q; Le Cerf, É; Bakkali-Hassani, B; Maury, C; Chauveau, G; Castilho, P C M; Saint-Jalm, R; Nascimbene, S; Dalibard, J; Beugnon, J
Abstract: We demonstrate the arbitrary control of the density profile of a two-dimensional Bose gas by shaping the optical potential applied to the atoms. We use a digital micromirror device (DMD) directly imaged onto the atomic cloud through a high resolution imaging system. Our approach relies on averaging the response of many pixels of the DMD over the diffraction spot of the imaging system, which allows us to create an optical potential with an arbitrary intensity profile and with micron-scale resolution. The obtained density distribution is optimized with a feedback loop based on the measured absorption images of the cloud. Using the same device, we also engineer arbitrary spin distributions thanks to a two-photon Raman transfer between internal ground states.